Church music in Nigeria: a historical trend (2013)
This paper traced the evolution of church music in Nigeria from the mid nineteenth century to date. It provided evidence that pattern of change within the music terrain in and outside the church is consistent with the theory of continuity and change. The various impacts which church music have made on the society on the one hand and the secularization of church music on the other were discussed. In particular, the gradual erosion of well established church music traditions inform of introduction of popular musical genres as well as consequent commercialization of gospel music were also brought to the fore. The paper, in conclusion, suggested practical steps to be taken by both the leadership of the church as well as all stakeholders in church music ministry in lifting church music in Nigeria to the next level while stressing its dynamic nature as a living art.